The burden of injuries in Iranian children in 2005 - Jafari Nahid; Shahraz Saeid; Pourmalek Farshad; Naghavi Mohsen; Delavar Bahram; Motlagh Mohammad (BMC, 2010)
Abstract Background Child injury is recognized as a global health problem. Injuries caused the highest burden of disease among the total population of Iran in 2003. We aimed to estimate the morbidity, mortality, and disease burden caused by child injuries in the 0- to 14-year-old population of Iran in 2005. Methods We estimated average age- and sex-specific mortality rates for different types of child injuries from 2001 to 2006 using Iran's death registration data. Incidence rates for nonfatal outcomes of child injuries in 2005 were estimated through a time- and place-limited sample hospital registry study for injuries. We used the World Health Organization's methods for estimation of years of life lost due to premature mortality and years lived with disability in 2005. Results Injuries were the most important cause of death in children ages 1 to 14, with 35, 33.4, 24.9, and 22.9 deaths per 100,000 in the 0-14, 1-4, 5-9, and 10-14 age groups respectively. Road transport injuries were responsible for the highest death rate per 100,000 population among all types of injuries in children, with 15.5 for ages 0-14, 16.1 for ages 1-4, 16.3 for ages 5-9, and 13.1 for ages 10-14. Incidence rates of injuries leading to hospitalization were 459, 530, and 439 per 100,000 in the 0-14, 1-4, and 5-14 age groups respectively. Incidence rates of injuries leading to outpatient care were 1,812, 2,390, and 1,650 per 100,000 in the same age groups respectively. Among injury types, falls and burns had the highest hospitalization and outpatient care incidence rates. Conclusions Injuries, particularly road transport injuries, were the most important health problem of children in Iran in 2003 and 2005. Strong social policy is needed to ensure child survival.